2019
DOI: 10.1002/adem.201900530
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Metal‐Enhanced Wire Mesh as a Stiffness Variable Material for Making Soft Robotics

Abstract: Stiffness variable materials are of great interests to many fields, especially in soft robotics. However, most materials require external voltage or high temperature to trigger the stiffness regulation process, which limits their applications in many situations, such as underwater. Herein, an easyoperating low-melting-point-metal enhancer is proposed, which can discretionarily regulate the stiffness of copper (Cu) wire mesh and greatly improve the performances of the target network-organized material. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that liquid metal has desirable wettability with other materials (e.g., Cu mesh), [169][170][171][172] thereby ensuring that the liquid metal can be closely attached to these soft solid materials while retaining the ability to be shaped. [173] Such a solid-liquid coupling strategy can help achieve the standing and shaping of liquid metal. In addition, the fast and controllable liquid metal solid-liquid phase changes are considered as beneficial for its standing and shaping.…”
Section: Liquid Metal-enabled Robotsmentioning
confidence: 99%
“…Previous studies have shown that liquid metal has desirable wettability with other materials (e.g., Cu mesh), [169][170][171][172] thereby ensuring that the liquid metal can be closely attached to these soft solid materials while retaining the ability to be shaped. [173] Such a solid-liquid coupling strategy can help achieve the standing and shaping of liquid metal. In addition, the fast and controllable liquid metal solid-liquid phase changes are considered as beneficial for its standing and shaping.…”
Section: Liquid Metal-enabled Robotsmentioning
confidence: 99%
“…Also, this special feature may provide a new strategy to reduce the shape recovery temperature. [21,22] This article describes 3D elastic polyurethane (PU) with metallic coating that can be programmed into stable, temporary shapes at body temperature. The shape of the 3D PU recovers rapidly and elastically when heated due to the ability of the coating to undergo a solid-liquid phase transition.…”
Section: Doi: 101002/adem202100372mentioning
confidence: 99%
“…Also, this special feature may provide a new strategy to reduce the shape recovery temperature. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Galinstan has been used, for example, as a coolant [2][3][4], a soft electronic material [5,6] and a lubricant [7,8]. EGaIn has been widely used in many areas, such as non-destructive contact in large-area junctions [9][10][11], nanomedicine carriers in drug delivery systems [12,13] and soft robotics [14][15][16]. To further enrich their functionalities, LM composites have been synthesized to build new material systems in which LMs/alloys are suspended as nanodroplets within a soft polymer matrix or mixed with other inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%